Analysis of the Influence of Taxpayer Understanding and Officer Socialization on Taxpayers' Compliance with PBB-P2 Payments in Villages in 2025 - Risa Dwi Puspasari; Khasanah Sahara; Rike Selviana Sari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study primarily aims to investigate the impact of taxpayer knowledge and information campaigns by tax officials on taxpayer compliance in paying property tax (PBB) in Bendo village. A quantitative descriptive approach was used, with data collected through questionnaires from 98 taxpayers, which were then evaluated using statistical tests. The results revealed that both tax knowledge and employee information campaigns have a positive and meaningful impact on taxpayer compliance, both individually and collectively. These findings suggest that strengthening public understanding of tax regulations and benefits, coupled with building tax awareness and compliance, and public communication theory highlight the role of education and the relationship between tax institutions and citizens. An innovative aspect of this study lies in the simultaneous examination of taxpayer knowledge and information campaigns in a PBB payment compliance scenario in a rural area. Practical recommendations for local governments are to design more interactive, participatory, and simple information campaign approaches to improve compliance.